"Proverbs and marriage in Yorubaland " (2008)
"Proverb is a very important oral genre among the Yoruba. It embellishes the traditions, values and customs of the people. This paper reviews the works of scholars on what proverb is, its form, how it reveals the socio-genetic nature, ethical values and philosophy about labour, family, friend etc of the Yoruba nation. A cursory look is taken at Yoruba proverbs relating to marriage. Twelve of such proverbs are collected, analyzed and discussed to reveal the sacredness and sanctity of marriage institution among the Yoruba. The paper observes that a matured is expected to marry, the in-laws should be revered, love and understanding should be the hallmark of a happy home while sexual promiscuity is detested. The paper offers recommendations on how to revive this moribund oral genre by teaching and examining it at primary and secondary schools and it concludes that knowledge of proverb helps to foster peace, unity love and progress in the Yoruba society."